2013
DOI: 10.5152/tpd.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hydatidosis in Slaughtered Animals in Iran

Abstract: It appears that sheep are the most important intermediate hosts for E. granolusus in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 16 publications
5
35
4
Order By: Relevance
“…This matter can be supported by the relationship between increasing age and risk of hydatidosis, since the most of older slaughtered livestock are often female. These results are compatible with the previous study which is conducted in Hamadan (8) and other reports area (10,11,15). In contrast to our study, the frequency of hydatid cyst in liver was higher than lungs in slaughtered animals that inspected in Yemen in 2012 (16).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This matter can be supported by the relationship between increasing age and risk of hydatidosis, since the most of older slaughtered livestock are often female. These results are compatible with the previous study which is conducted in Hamadan (8) and other reports area (10,11,15). In contrast to our study, the frequency of hydatid cyst in liver was higher than lungs in slaughtered animals that inspected in Yemen in 2012 (16).…”
supporting
confidence: 92%
“…Another finding in this study showed that 5.3% of the slaughtered cattle were infected with CE, more than sheep and goats. In Iran, CE in cattle has ranging from 1% to 28% with the mean of 12% based on some previous investigations (8,9,11,12). However, there is a report of high prevalence on cattle hydatidosis (38%) in Ardabil province (10).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Another epidemiological study of hydatidosis in the camels from different regions of Iran showed that 42.8 % in Khorasan Razavi Province, 17.8 % in Yazd province, 22.8 % in South Khorasan province, 4.28 % in Semnan province, and 12.14 % in Sistan and Baluchestan province were positive (Moghaddas et al 2014). Prevalence rate of hydatidosis in sheep, goats, cattle and calf was 16.4, 3.1, 6.5 and 8.2 %, respectively in Isfahan province, Iran (Azami et al 2013). Based on our knowledge, there is no previous study regarding the prevalence of equine hydatidosis in Iran.…”
Section: Introductionmentioning
confidence: 79%
“…Although abattoir surveys have limitations, they are an economical way of gathering information on livestock disease. Also, a feedback from the slaughterhouse to the individual farm is of great value in the field of preventive medicine (Azami et al 2013).…”
Section: Discussionmentioning
confidence: 99%